IDENTIFIKASI STRUKTUR BAWAH PERMUKAAN MENGGUNAKAN METODE MAGNETOTELLURIK 2D DI DAERAH CEKUNGAN BINTUNI SEBAGAI POTENSI HIDROKARBON - Ririn Yulianti; Syamsurijal Rasimeng; Karyanto Karyanto; Hidayat Hidayat; Noor Muhammad Indragiri (Jurnal Geofisika Eksplorasi, 2018)
Magnetotelluric research was done in hydrocarbon prospect area of Bintuni basin, West Papua province. The purpose of this research is to identificate hydrocarbon prospect in subsurface structure using 2D resistivity section. Data processing step for the research are; (i) Data transformation from time domain to frequency domain using Fourier transformation. (ii) Filtering process using Robust No Weight, Robust Rho Variance and Robust Ordinary Coherency. (iii) XPR selection and formatting data into EDI file. (iv) 2D resistivity section modeling using inversion. The result of this research based on 2D resistivity section in Klasafat formation have resistivity value about 1 – 20 Ωm. From 0 until 1000 meter below the surface the main lithology is claystone that identified as caprock. Kemblengan formation have resistivity value about 20 – 90 Ωm in 3500 meter under surface with main lithology lime-sandstone and identified as a reservoir. Tipuma formation have resistivity value about 0.62 – 2 Ωm in 8000 meter under surface with main lithology claystone. Kemun formation have resistivity value about 20 – 32 Ωm in 6000 meter under surface with main lithology sandstone and identified as a basement.